Social anxiety disorder and antibodies against glial cells in the cerebrospinal fluid - Judith Weiser; Alexander Rau; Katharina von Zedtwitz; Bernd Feige; Kathrin Nickel; Simon J. Maier; Raphael J. Dressle; Nils Venhoff; Ludger Tebartz van Elst; Miriam A. Schiele; Katharina Domschke; Harald Prüss; et al. (Brain, Behavior, & Immunity - Health)
Introduction: Autoimmune social anxiety disorders have not yet been described in the literature. Methods: Therefore, this case of a patient with possible autoimmune-mediated social anxiety disorder is presented. Due to treatment resistance and high serum streptococcal antibody levels, a comprehensive diagnostic work-up was performed. Results: The 19-year-old female patient presented with predominant social anxiety disorder and secondary depression. Testing for all known characterized neuronal and glial IgG antibodies identified slightly positive (“+”) recoverin IgG antibodies only in the serum (using an immunoassay). Cerebrospinal fluid (CSF) analysis using a tissue-based assay on unfixed mouse brain slices revealed moderate immunoglobulin G (IgG) anti-nuclear binding and a specific strong IgG binding against cell nuclei of the Bergmann glia in the cerebellum. No clear pathology was noted in conventional magnetic resonance imaging (MRI), voxel-based morphometry, and cerebral blood flow. Diffusion microstructure imaging (DMI) revealed a substantial reduction of the intraneurite volume fraction in the cerebellar gray and white matter. This was accompanied by a compensatory increase in free fluid and the extra-neurite volume fraction. Alterations in the striatum were also observed with DMI. Electroencephalography (EEG) showed intermittent generalized slowing with underlying left frontal, right temporal, and left temporo-occipital components (detected via independent component analysis of the EEG). The [18F]fluorodeoxyglucose positron emission tomography of the whole body detected a slight polyserositis and no malignant tumor. Discussion: This is the first description of a case with evidence of a possible antibody-mediated cerebellar dysfunction associated with social anxiety disorder. The testing for all characterized neuronal/glial antibodies showed only weakly positive recoverin antibodies in the serum, which, however, were not detectable in the CSF. Therefore, novel CSF antibodies directed against cell nuclei of the Bergmann glia in the cerebellum could be assumed. DMI alterations in the cerebellum were in principle compatible with neuroinflammation with edematization and cellular activation. In addition, the further DMI alterations in the striatum and the fronto-temporal generators of EEG slowing suggest an involvement of the “anxiety network”. Further immunopsychiatric research in anxiety disorders might contribute to identifying an autoimmune subtype and potentially immunomodulatory treatment options.